Evaluation of the main elements in the leading proposals to phase out the multi-fibre arrangement - Erzan, Refik (World Bank WashingtonUS, 1990)
Gives a brief account of the phaseout proposals tabled by developed and developing countries and analyzes the historical MFA quota growth in the EC and the US. Examies a phaseout within the framework of the MFA which relies on accelerated quota growth based on the historical record. Looks at a phaseout based on global quotas along the lines of the US proposals. Underlines some of the critical issues the negotiators might have to address in their future consideration of the two leading proposals.